(untitled) (Colloquia Comparativa Litterarum, 2025)
The paper is dedicated to the history of translation of Sophocles’ seminal tragedy Oedipus the King in Bulgaria. It studies the different strategies of translation that have been adopted by Bulgarian authors, when rendering the Greek word τυˊχη in contemporary Bulgarian language. In comparing the various translational versions of a short passage from the 3rd epeisodion, and having in mind the translators’ background and decisions, the paper argues that the instance of Oedipus the King is indicative of the productive power of translation. The comparison shows how displacements and shifting of meaning in the process of translation could bring about new, unexpected effects of meaning. This situation is also brought about by the specific way of reception of Ancient literature in Bulgaria, since not all of the translators have used the original in their work.